Efficacy of Drumstick Tree (Moringa oleifera) Leaves Powder on Lipid Profile and Hematological Indices in Chickens on a High Fat Diet - Aisha Saleem,; Irum Naureen,; Muhammad Naeem, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Moringa oleifera belongs to the Moringaceae family and genus Moringa. Moringa oleifera has many beneficial pharmaceutical and nutritional properties. The present study aimed to investigate the effects of dietary supplements of Moringa oleifera leaves powder after consumption of a high-fat diet on cholesterol TG, HDL, LDL, VLDL and hematological parameters such as Hb, MCV, MCH, MCHC, PCV, RBCs, WBCs, PLT neutrophil, heterophil and lymphocytes count in chicks. Golden Misri Chickens were divided into 4 groups: Group 1 (the Control group) was given Feed-13. Group 2 (Experimental Group) was given Feed-13 and mustard oil (high-fat diet) Group 3 (experimental Group) was given Feed-13 + mustard oil and 1.5% Moringa oleifera leaves powder. Group 4 (experimental Group) was given Feed-13 and 1.5% of Moringa oleifera leaves powder for four weeks. The results of the current study showed a significant (p < 0.05) increase in body weight in Experimental Group 3. Experimental group 3 showed a significant increase in levels of HDL, TG, RBCs, and Hb, while significantly decreased (p > 0.05) in LDL, TLC, WBCs, MCHC, MCV, MCH, TC, TP, Monocytes count, neutrophil count, and platelet counts. Moringa oleifera supplementation showed a significant reduction in cholesterol, LDL, and TC levels. The findings of this study demonstrated that powdered Moringa oleifera is a beneficial and effective dietary supplement that increases HDL, TG, Hb, and RBCs, and decreases cholesterol levels.